2007
DOI: 10.4064/cm108-1-9
|View full text |Cite
|
Sign up to set email alerts
|

On the arithmetic of arithmetical congruence monoids

Abstract: Let N represent the positive integers and N 0 the non-negative integers. If b ∈ N and Γ is a multiplicatively closed subset of Z b = Z/bZ, then the set H Γ = {x ∈ N | x + bZ ∈ Γ } ∪ {1} is a multiplicative submonoid of N known as a congruence monoid. An arithmetical congruence monoid (or ACM) is a congruence monoid where Γ = {a} consists of a single element. If H Γ is an ACM, then we represent it with the notation M (a, b) = (a + bN 0) ∪ {1}, where a, b ∈ N and a 2 ≡ a (mod b). A classical 1954 result of James… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…If d = 1 then we call M a,b regular and if d > 1, we call it singular. An elementary argument (see [3,Lemma 2.1]) shows that regular ACMs are precisely the Hilbert monoids described above. Singular ACMs are further characterized as being either local or global depending on whether d has one or more distinct prime factors.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…If d = 1 then we call M a,b regular and if d > 1, we call it singular. An elementary argument (see [3,Lemma 2.1]) shows that regular ACMs are precisely the Hilbert monoids described above. Singular ACMs are further characterized as being either local or global depending on whether d has one or more distinct prime factors.…”
Section: Introductionmentioning
confidence: 99%
“…Arithmetical congruence monoids have been addressed recently in the literature in [2] and [3] where the factorization properties of these monoids are explored. In particular, in [3,Theorem 2.4] it is shown that the elasticity of factorization (see [1] or [10] for a definition) of M a,b is finite if and only if M a,b is regular or local.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations